Are we ready for Taenia solium cysticercosis elimination in sub-Saharan Africa?. Issue 1 (20th April 2016) - JOHANSEN, MARIA VANG; TREVISAN, CHIARA; GABRIËL, SARAH; MAGNUSSEN, PASCAL; BRAAE, UFFE CHRISTIAN
SUMMARY: The World Health Organization announced in November 2014 at the fourth international meeting on 'the control of neglected zoonotic diseases – from advocacy to action', that intervention tools for eliminating Taenia solium taeniosis/cysticercosis (TSTC) are in place. The aim of this work was to elucidate theoretical outcomes of various control options suggested for TSTC elimination in sub-Saharan Africa (SSA) over a 4-year period. Our current knowledge regarding T. solium epidemiology and control primarily builds on studies from Latin America. A simple transmission model – built on data from Latin America – has been used to predict the effect of various interventions such as mass treatment of humans, vaccination and treatment of pigs, and health education of communities, potentially leading to change in bad practices and reducing transmission risks. Based on simulations of the transmission model, even a 4-year integrated One Health approach fails to eliminate TSTC from a small community and in all simulations, the prevalence of human taeniosis and porcine cysticercosis start to rise as soon as the programmes end. Our current knowledge regarding transmission and burden of TSTC in SSA is scarce and while claiming to be tool ready, the selection of diagnostic and surveillance tools, as well as the algorithms and stepwise approaches for control and elimination of TSTC remain major challenges.